Effect of Cofee Residue and Cropping System on Crop Yield and Physicochemical Properties of the Soil in Southern Ethiopia - Workayehu, Tenaw (2005)
Dumping and burning of coffee residue brought a serious environmental problem. On the other hand, low soil fertility due to multiple cropping with low input coupled with moisture stress results in decline in production. This study was conducted to evaluate decomposition and mineralization of N from coffee residue, and its effect on soil physicochemical properties, crop yield, and apparent nutrient balance. Decomposition and release of N in soil was studied using five periods of incubation (0, 30, 60, 90, and 120 days) and four rates of residue (0, 3, 6, and 9 Mg ha-') in pot experiment. The same rates of residue and four rates of N fertilizer (0, 30, 60, and 90 kg ha-'), urea as source, were studied under field condition. In the pot experiment, coffee residue decomposed in two phases: viz. an initial faster phase, and a later slow rate of decay. Decomposition rate (KD) was controlled by lignin (L) and nitrogen (N) contents, and L/N ratio ( R =~ 0.975**, n = 36). Immobilization of soil N persisted for the entire 120 days, and release of N was controlled by lignin and cellulose contents, residue N and L/N ratio ( R=~ 0 .982**). In the field, coffee residue alone significantly increased the mean uptake of N (106%), P (165%), and K (93%) in both maize and haricot bean, and its combination with N fertilizer enhanced the uptake by 143, 172 and 102%, respectively, compared to the control (without both residue and N fertilizer). Water use efficiency (WUE) increased significantly by 78% for maize and land equivalent ratio (LER) by 7% using coffee residue alone; and by 95% for total WUE and 16% for LER using residue along with N fertilizer. Efficiency of intercrop was 13% higher than sole cropping. Grain yield of maize with residue only varied between 52 and 88% of the sole maize yield (4,330 kg ha-'). In both pot and field experiments, soil amended with coffee residue showed increase in moisture content, total N (TN) and OC content. In the field study, the residue increased the physicochemical properties of the soil such as moisture (38%), TN (7.6%), and OC (8%) compared to the control. Intercropping increased soil moisture (3%), available P (8%) and K (15%) but reduced soil N (19%) and OC (4%) relative to the contents in sole maize. Depletion of 20 and 70 kg N ha-' was obtained in soil treated with coffee residue and N fertilizer alone, respectively. On the other hand, a positive balance of 19.4 kg N ha-' was obtained from application of coffee residue followed by N fertilizer. The loss of K was high at 289 kg ha-' with coffee residue only and at 159 kg h i ' from coffee residue followed by N fertilizer. Application of 9 Mg ha-' coffee residue and 9 Mg ha-' coffee residue with 90 kg N ha-' gave the highest maize grain yields (3,807 and 4,133 kg ha-', respectively) and monetary values of 1,834 and 2,367 birr ha-' (lUSD= 8.40 Ethiopian birr), respectively, indicating the economic using coffee residues. Amelioration of soil with coffee residue and/or N fertilizer provided improvement in soil physicochemical properties and crop yields. Therefore, utilization of coffee residue would not only provide an alternative source of plant nutrients but also alleviates soil fertility and reduce environmental pollution problems.